Digital cholangioscopy can detect residual biliary stones missed by occlusion cholangiogram in ERCP: a prospective tandem study - Sejpal, Divyesh V.; Trindade, Arvind J.; Lee, Calvin; Miller, Larry S.; Benias, Petros C.; Inamdar, Sumant; Singh, Gurshawn; Stewart, Molly; George, Benley J.; Vegesna, Anil K. (Endoscopy International Open, 2019)
Background and study aims After stone removal in endoscopic retrograde cholangiopancreatography (ERCP), an occlusion cholangiogram (OC) is performed to confirm bile duct clearance. OC can miss residual stones that can lead to recurrent biliary symptoms. The aim of this study was to assess if digital peroral cholangioscopy (POC) increased the diagnostic yield of residual biliary stones that are missed with OC.Patients and methods Patients having ERCP performed for choledocholithiasis were enrolled into the study only if they had one of the following criteria: dilated bile duct ≥ 12 mm and/or if lithotripsy was being performed. An OC was performed to confirm duct clearance after removal of stones followed by POC, based on inclusion criteria. The incremental yield of biliary stones missed by OC but confirmed by POC was then measured. A total of 96 POC procedures were performed on 93 patients in two tertiary care centers.Results Residual biliary stones were found in 34 % of cases. The average bile duct size in cases with residual stones was 15.1 mm ± 0.7 mm. One- to three-mm stones were found in 41 % of cases, 4- to 7-mm stones in 45 % of cases, and ≥ 8-mm stones in 14 % of cases. Lithotripsy was performed in 13 % of cases and was significantly associated with residual stones (30 % vs. 3 %, P < 0.001).Conclusions Occlusion cholangiogram can miss residual stones in patients with dilated bile ducts and those receiving lithotripsy. Digital POC can increase the yield of residual stone detection in these patients and should be considered to confirm clearance of stones. (ClinicalTrials.gov-NCT03482375).